Model Kurikulum Pendidikan Layanan Khusus Pendidikan Non Formal untuk Daerah Konflik - Kamin Sumardi (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2008)
Curriculum is one important component in education, as specially in learning process. Curriculum must support all the student need, because of it, we need a special curriculum. Every conflict has a different characteristic, but the effect on the child education has the same meaning. Because of that, we have to arrange one of curriculum development and the evaluation more specific by using a special service especially in non forma education. Special service education in non formal education (PLK-PNF) for conflict area, which has a base differentiation in learning process. This special service education has a double mission, for education and ti handle the side effect of conflict as physically and also psychologist.